Cu-based bimetallic catalysts for CO2 reduction reaction - Wang, Xi-Qing; Chen, Qin; Zhou, Ya-Jiao; Li, Hong-Mei; Fu, Jun-Wei; Liu, Min (Advanced Sensor and Energy Materials, 2022)
Electrocatalytic CO₂ reduction reaction (CO₂RR) is one of the effective means to realize CO₂ resource utilization. Among the high-efficiency metal-based catalysts, Cu is a star material profiting from its ability for CO₂ reduction into valuable hydrocarbon products. However, due to the difficulty in activating CO₂ and regulating intermediate adsorption/desorption properties, the CO₂RR activity and selectivity of Cu-based catalysts still cannot meet the requirements of industrial applications. The design of Cu-based bimetallic catalysts is a potential strategy because the introduction of the second metal can well promote the activation of CO₂ and break the linear scaling relationship in intermediate adsorption/desorption. In this review, the synergistic enhancements of Cu-based bimetals on CO₂ activation and intermediate adsorption/desorption are analyzed in detail, including the advantages caused by the morphology of Cu-based bimetallic catalysts, the local electric field effect induced by the special nanoneedle structure, the interface engineering (strain effect, atomic arrangement, interface regulation), and other particular effects (electronic effect and tandem effect). Finally, the challenges and perspectives on the development of Cu-based bimetallic catalysts for CO₂ reduction are proposed.